Yield response of soybean [Glycine max (L.) Merrill] to liming and manuring in acidic soil of Manipur: Yield response of soybean [Glycine max (L.) Merrill] to liming and manuring in acidic soil of Manipur - T SUNANDA DEVI; NILIMA KARAM; H NANITA DEVI; L SOPHIA DEVI (Journal of Oilseeds Research, 2020)
Field experiment was conducted in acidic soil. Application of farm yard manure @ 2.5 t/ha significantly enhanced the soybean yield and yield attributes. Soybean yield and yield attributes linearly increased as the levels of lime increased up to 600 kg/ha and then declined. Application of FYM @ 2.5 t/ha along with 600kg/ha of lime recorded maximum seed yield and yield components of soybean.